Synthesis and Classical Pathway Complement Inhibitory Activity of C7-Functionalized Filifolinol Derivatives, Inspired in K-76 Cooh - Torres-Gaona, M (2012)
A series of carboxylic acids carrying various functionalization on C-7 of their common 3H-spiro[benzofuran-2,1?-cyclohexane] skeleton were synthesized from filifolinol, as analogs of the natural Complement inhibitor K-76 COOH. In order to probe the relevance of the C-7 functionalization on their bioactivity, the ability of the analogs to inhibit Complement activation through the classical pathway was determined. The observed results suggest that functionalization of C-7 can modulate the inhibitory activity of the tested compounds. The 7-trifluoromethyl derivative was the compound with the lowest IC50 value among the tested analogs (IC50 = 100 ?M), being more potent than K-76 COOH (IC50 = 570 ?M). © 2012 Elsevier Masson SAS. All rights reserved.